Prevalence of Thrombocytopenia in Women during Third Trimester of Pregnancy - Memoona Hanif, Tahira Akhtar, Safia Ashraf, Andeela Shahzadi, Hifza Rani (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the prevalence of thrombocytopenia in women during third trimester of pregnancy. Study Design: Cross-sectional study. Place and Duration: Department of Obstetrics and Gynaecology Department, District Headquarter Hospital, Gujranwala, from April 2022 to October 2022. Methodology: Women with third trimester of pregnancy (aged 18-45 yeas) were analyzed. Two milliliters of venous blood was collected and sent to institutional laboratory for complete blood count evaluation. Frequency of thrombocytopenia was noted. Thrombocytopenia was defined as the platelets count <150×106/mm3. Results: In a total of 150 women, the mean age was 28.17±4.61 years and 101 (67.33%) women were aged between 18-30 years. The mean gestational age was 32.88±1.78 weeks while the mean parity was 2.84±1.02. The mean platelets count was 213×106/mm3±78.33×106/mm3. Thrombocytopenia in women during third trimester of pregnancy was found in 15 (10.0%) women. Practical Implications: Early detection of gestational thrombocytopenia and careful calculation of risks and preemptive management can be done in order to reduce the fetomaternal morbidity and mortality of patients. Conclusion: The prevalence of thrombocytopenia in women during 3rd trimester of pregnancy was 10.0%. Keywords: Gestational age, parity, pregnancy, third trimester, thrombocytopenia.